Improving reading skills through internet schoology for vocational high school - Sri Komaryati (Journal of English Language and Pedagogy, 2020)
The objectives of this study are (1) to describe the process of implementation of Internet Schoology in teaching reading; (2) to find out the result of the implementation of Internet Schoology in teaching reading. This research belongs to Classroom Action Research proposed by Kemmis and Mac Taggart (1999). It consisted of four steps. They are planning, action, observation, and reflection. The research used inquiry-based instruction for the teaching method and the internet Schoology as the source of online media. This research was conducted in two cycles. The process of the implementation of Schoology was opening, introduction, exploration, elaboration, confirmation, and closing. In the opening, the researcher greeted the students and praying. The students were introduced with the used of Schoology, the topic was stated, and the researcher explains the learning objectives in the introduction. In elaboration, students did an assignment, to answer questions based on a text. In exploration, the teaching and learning were about to identify the topic of the text, identify the vocabulary or difficult words, identify the main idea and specific info of the text, and identify the grammar used in the text. In confirmation, the students got the answer to their assignment. The method of inquiry-based instruction was applied to internet Schoology. The result shows that the students were enthusiastic and motivated to learn reading using Schoology. There was an improvement from cycle 1 to cycle 2. The using of internet Schoology improved the students reading ability, especially in mastering vocabulary.